2005
DOI: 10.1189/jlb.0504273
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional characteristics of CD34+ cells are related to their anatomical environment: is their versatility a prerequisite for their bio-availability?

Abstract: Human CD34+ hematopoietic progenitors (HP) are mainly resident in adult bone marrow (BM). However, their recent revelation in nonhematopoietic tissues implies their circulation through peripheral blood (PB). The intimate mechanisms of this physiological process are not yet understood. Our results showed that steady-state CD34+ HP exhibit a differential phenotypic profile according to their BM versus PB localization. We demonstrated that this phenotype could be modulated by incubation in the presence of their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…It has been shown that endothelial progenitor cells have enhanced angiomyogenic capacity when pre-conditioned with VEGF 165 , brain-derived nerve growth factor and other endothelial signals [26,27]. It has also been demonstrated that upon incubation with mononuclear cells, the migration capacity of isolated peripheral blood CD34 + cells increases [16]. Similarly, in the present study, migration of CD133 + cells was significantly increased upon co-culture with the CD133 À fraction.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It has been shown that endothelial progenitor cells have enhanced angiomyogenic capacity when pre-conditioned with VEGF 165 , brain-derived nerve growth factor and other endothelial signals [26,27]. It has also been demonstrated that upon incubation with mononuclear cells, the migration capacity of isolated peripheral blood CD34 + cells increases [16]. Similarly, in the present study, migration of CD133 + cells was significantly increased upon co-culture with the CD133 À fraction.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, bone marrow monocytic lineage cells can adhere to regions of injured endothelium and accelerate re-endothelialization by endothelial progenitors [14,15]. Recently, it was demonstrated that interactions with the cellular microenvironment influence the surface receptor expression and function of CD34 + cells in the peripheral circulation [16]. The relationship between the cell types within the peripheral blood and how they relate to angiogenic potential of CD133 + cells remains to be investigated, and constitutes a focus of the present study.…”
Section: Introductionmentioning
confidence: 96%
“…Consistent with this concept is the suggestion that "supernatants of leukapheresis products" from G-CSF MPB may sensitize HPC to SDF-1-dependent migration and consequently may contribute to the improved marrow homing of MPB cells. [48,59] The molecular mechanisms enabling this behavior remain to be elucidated. Alternatively, it is conceivable that after G-CSF stimulation the cells with inherently greater migratory propensity preferentially leave the marrow, to accumulate in MPB.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several limitations to purifying HSCs/HPCs exclusively based on cell surface determinants, because they may vary according to developmental stage, stem cell source, cell cycle status, regenerative process, and experimental conditions [1,32]. Several teams have, therefore, introduced novel properties, such as Hoechst exclusion or ALDH activity, to purify HSCs/HPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Sorting the CD34 þ CD38 Low/À cell population has proven to be extremely useful for the characterization of human HSC and hematopoietic progenitor cell (HPC) cell compartments. However, the heterogeneity of membrane antigens [1] and their variable expression as well as the low potential of purified populations to repopulate BM have made HSC/HPC definition based solely on cell surface phenotype questionable. Recently, several groups have attempted to develop new purification strategies based on the unique biochemical or metabolic activity of these cells.…”
Section: Introductionmentioning
confidence: 99%